IMPACTS OF ABRUPT CLIMATE CHANGE ON NATIONAL SECURITY: THE UNITED STATES PERSPECTIVE ON HOMELAND DEFENSE IN THE NORTH AMERICAN ARCTIC - LAVORIO, AGATA (Università degli Studi di Milano, 2021)
The purpose of this research is to assess whether abrupt climate change (intended as a major change in physical geography) can be a driver for national security planning. To demonstrate that geography still affects national security planning, this research retrieves the concept of environmental causality applied to an empirical case – that of US adaptation to climate change for homeland defense in an area called “The North American Arctic.” Consequently, the research frames the adaptation process into a causal mechanism where proximity to climate change effects (experienced by some actors of the defense domain) is the cause explaining the change of the United States (US) geostrategic posture in the Arctic. Indeed, one of the most severe impacts climate change is having on US national security regards its homeland defense in the Arctic. Traditionally, the US was granted continental defense thanks to its invulnerability in the Northern hemisphere. Still, with the Arctic gatekeeper's collapse caused by climate change, US homeland defense may be at stake. According to the environmental probabilistic perspective (here adopted), the fact that climate change is shaping the physical conformation of the Arctic is not necessarily acknowledged by policy-makers or military leaders since geography does not dictate predetermined outcomes. It follows that to consider climate change as a driver, it must be found consistent evidence that actors are including climate change in national security planning and reacting to its impacts. To do so, the research reconstructs the process of adaptation to climate change in the North American Arctic from the point of view of the actors involved in homeland defense and looks for the cause and the contextual factors of the process. The research then provides systematic qualitative data (e.g., strategies, reports, grey literature, journal articles, newspaper interviews) triangulated with some élite interviews with climate security experts and government officials. Through the framing of ...